Can tDCS enhance item-specific effects and generalization after linguistically motivated aphasia therapy for verbs? - de Aguiar, Vânia; Bastiaanse, Roelien; Capasso, Rita; Gandolfi, Marialuisa; Smania, Nicola; Rossi, Giorgio; Miceli, Gabriele (Frontiers in Behavioral Neuroscience, 2015)
Background. Aphasia therapy focusing on abstract properties of language promotes both item-specific effects and generalization to untreated materials. Neuromodulation with transcranial Direct Current Stimulation (tDCS) has been shown to enhance item-specific improvement, but its potential to enhance generalization has not been systematically investigated. Here, we test the efficacy of ACTION (a linguistically motivated protocol) and tDCS in producing item-specific and generalized improvement in aphasia. Method. Nine individuals with post-stroke aphasia participated in this study. Participants were pre-tested with a diagnostic language battery and a cognitive screening. Experimental tasks were administered over multiple baselines. Production of infinitives, of finite verbs and of full sentences were assessed before and after each treatment phase. Nonword repetition was used as a control measure. Each subject was treated in two phases. Ten daily 1-hour treatment sessions were provided per phase, in a double-blind, cross-over design. Linguistically-motivated language therapy focusing on verb inflection and sentence construction was provided in both phases. Each session began with 20 minutes of real or sham tDCS. Stimulation site was determined individually, based on MRI scans. Results. Group data showed improved production of treated and untreated verbs, attesting the efficacy of behavioral treatment, and its potential to yield generalization. Each individual showed significant item-specific improvement. Generalization occurred in the first phase of treatment for all subjects, and in the second phase for two subjects. Stimulation effects at the group level were significant for treated and untreated verbs altogether, but a ceiling effect for Sham cannot be excluded, as scores between real tDCS and Sham differed only before treatment. Conclusion. Our data demonstrate the efficacy of ACTION and suggest that tDCS may enhance both item-specific effects and generalization.